The 2002 designing streets for people report ideas and recommendations on how to transform our streets into places for people, for business, for pleasure, for shopping, for talking, for movement - for life : the final report of the Designing streets for people inquiry. (Thomas Telford, 2002)
Why are streets as they are? Can they be better managed and add more to the quality of life for those who use them, live in them, or work in them? This report looks at actions needed to improve our street environment over the first 25 years of the new millennium.